Gene & Cell Therapy for Cancers: The Promise of Chimeric Antigen Receptor (CAR)-T Cells - Taruna Ikrar (The ASEAN Journal of Military and Preventive Medicine, 2024)
The pharmacology of cell and genetic therapy represents a highly advanced and contemporary treatment technology, capable of addressing the root causes of numerous diseases with remarkable accuracy and precision at the DNA and molecular levels. Genetic technology aims to develop treatments for genetic disorders caused by inherited genetic mutations, which affect millions of people worldwide and are often life-threatening terminal illnesses. Moreover, pharmacologists and genetic biologists are striving to treat hereditary disorders. By integrating cell and genetic molecular biology, scientists have developed Chimeric Antigen Receptor T-Cell (CAR-T) technology, which has been approved for the treatment of blood cancer. Cell-based and genetic therapy is a groundbreaking therapeutic approach poised to become a cornerstone in the future treatment of degenerative and malignant diseases, particularly cancer, congenital or genetic disorders.